Roles of laboratories and laboratory systems in effective tuberculosis programmes - John C Ridderhof; Armand van Deun; Kai Man Kam; PR Narayanan; Mohamed Abdul Aziz (The World Health Organization, 2007)
Laboratories and laboratory networks are a fundamental component of tuberculosis (TB) control, providing testing for diagnosis, surveillance and treatment monitoring at every level of the health-care system. New initiatives and resources to strengthen laboratory capacity and implement rapid and new diagnostic tests for TB will require recognition that laboratories are systems that require quality standards, appropriate human resources, and attention to safety in addition to supplies and equipment. To prepare the laboratory networks for new diagnostics and expanded capacity, we need to focus efforts on strengthening quality management systems (QMS) through additional resources for external quality assessment programmes for microscopy, culture, drug susceptibility testing (DST) and molecular diagnostics. QMS should also promote development of accreditation programmes to ensure adherence to standards to improve both the quality and credibility of the laboratory system within TB programmes. Corresponding attention must be given to addressing human resources at every level of the laboratory, with special consideration being given to new programmes for laboratory management and leadership skills. Strengthening laboratory networks will also involve setting up partnerships between TB programmes and those seeking to control other diseases in order to pool resources and to promote advocacy for quality standards, to develop strategies to integrate laboratories' functions and to extend control programme activities to the private sector. Improving the laboratory system will assure that increased resources, in the form of supplies, equipment and facilities, will be invested in networks that are capable of providing effective testing to meet the goals of the Global Plan to Stop TB.